Parental divorce and generalized trust - Tarja K. Viitanen (Institute for the Study of Labor (IZA), 2011)
This paper examines the effect of parental divorce during childhood on generalized trust later on in life using Australian HILDA panel data. The dependent variable is composed of answers to the statement: Generally speaking, most people can be trusted. The main explanatory variables include the occurrence of parental divorce for the whole sample and the age at which parents divorced for the sub-sample. The analysis is conducted using random effects ordered probit, correlated random effects ordered probit and instrumental variables ordered probit models. The results indicate that the level of generalized trust is significantly affected by parental divorce for both men and women. This main result is very robust to alternative specifications. Furthermore, there is a marginally significant effect on the expressed level of generalized trust due to age at which parents divorced for women, but not men.
urn:nbn:de:101:1-201108152058
Keywords: J12; J13; H8; Z13; 330; parental divorce; generalized trust; HILDA; random effects ordered probit; instrumental variables ordered probit